The IMF as a function of supersonic turbulence - Bertelli Motta, Clio; Clark, Paul C.; Glover, Simon; Klessen, Ralf S.; Pasquali, Anna (Arxiv, 2016)
Recent studies seem to suggest that the stellar initial mass function (IMF) in early-type galaxies might be different from a classical Kroupa or Chabrier IMF, i.e. contain a larger fraction of the total mass in low-mass stars. From a theoretical point of view, supersonic turbulence has been the subject of interest in many analytical theories proposing a strong correlation with the characteristic mass of the core mass function (CMF) in star forming regions, and as a consequence with the stellar IMF. Performing two suites of smoothed particles hydrodynamics (SPH) simulations with different mass resolutions, we aim at testing the effects of variations in the turbulent properties of a dense, star forming molecular cloud on the shape of the system mass function in different density regimes. While analytical theories predict a shift of the peak of the CMF towards lower masses with increasing velocity dispersion of the cloud, we observe in the low-density regime the opposite trend, with high Mach numbers giving rise to a top-heavy mass distribution. For the high-density regime we do not find any trend correlating the Mach number with the characteristic mass of the resulting IMF, implying that the dynamics of protostellar accretion discs and fragmentation on small scales is not strongly affected by turbulence driven at the scale of the cloud. Furthermore, we suggest that a significant fraction of dense cores are disrupted by turbulence before stars can be formed in their interior through gravitational collapse. Although this particular study has limitations in its numerical resolution, we suggest that our results, along with those from other studies, cast doubt on the turbulent fragmentation models on the IMF that simply map the CMF to the IMF.